Nonsurgical Treatment of Maxillary Deficiency Using Tongue Guard Appliance: A Case Report - Farzaneh Ahrari; Neda Eslami (Journal of Dental Research, Dental Clinics, Dental Prospects, 2011)
The present report describes orthodontic treatment of a patient with skeletal Class III malocclusion and maxillary hypoplasia. To correct the retrusive maxilla, the treatment plan included an intra-oral removable device. It had the advantages of good patient cooperation, ease of construction and effective modification. Forward growth of the maxilla, minimal downward and backward rotation of the mandible and improved facial profile esthetics were achieved.